82P Real-world survival with first-line (1L) chemotherapy in patients (pts) with advanced non-small cell lung cancer (aNSCLC). (15th December 2019) - Waterhouse, D; Betts, K A; Zhao, J; Rao, S; Gupte-Singh, K; Rutstein, M; Higashi, M K; Schwartzberg, L
Abstract: Background: Real-world (RW) data are complementary to clinical trial data in bridging information gaps and facilitating decision making. This study compared overall survival (OS) of 1L chemotherapy (chemo) for aNSCLC in RW with pooled OS estimated from a meta-analysis of chemo arms from randomized clinical trials (RCT). Methods: In the meta-analysis, identified phase 3 RCTs reported OS for 1L carbo/cisplatin-chemo regimens in aNSCLC (2006 to 2019, most enrolled pts after 2010). In the RW analysis, treatment-naïve pts with aNSCLC receiving 1L chemo were identified from the Flatiron Health database (Jan 2011 to Mar 2019) to ensure adequate follow up. Four cohorts were selected based on histology and PD-L1 tumor proportion score (TPS, table). Other eligibility criteria (age, ECOG performance status, biomarker status) were applied to approximate the common inclusion/exclusion criteria used in the RCTs. OS was defined as time from 1L chemo initiation until death of any cause. Results: The non-squamous and squamous RW cohorts regardless of PD-L1 level had median OS (95% CI) 12.9 (11.5 - 14.2) months and 12.4 (11.6 - 13.3) months, respectively; comparable to the meta-analysis (tableTable: ). In the TPS ≥1% cohort, median OS was 18.1 (14.1 - 20.7) months, longer than the meta-analysis estimate. In the TPS ≥50% cohort, median OS was 20.3 (14.6 - 29.5) months, also longer than the median OS in the meta-analysis. Conclusion: RW OS in broad histology-based populations of 1L chemo pts was similar to meta-analysis estimates from corresponding trial populations. However, RW OS in TPS-based populations, where biomarker information is more commonly available in recent cohorts, was numerically longer than in the corresponding meta-analysis trial populations. Additional analyses are planned to assess IO-chemo in RW and to determine the influence of post-progression immunotherapy and imbalances in prognostic factors on chemo treatment group outcomes. Legal entity responsible for the study: Bristol-Myers Squibb. Funding: Bristol-Myers Squibb. Disclosure: D. Waterhouse: Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Speaker Bureau / Expert testimony: Genentech/Roche; Honoraria (self), Speaker Bureau / Expert testimony: Lilly; Advisory / Consultancy: Abbvie; Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Jannsen; Advisory / Consultancy: Amgen; Advisory / Consultancy: McGivveny Global. K.A. Betts: Research grant / Funding (institution), Keith Betts is an employee of Analysis Group, which received funding from Bristol-Myers Squibb for the conduct of the study: Bristol-Myers Squibb. J. Zhao: Research grant / Funding (institution), Employee of Analysis Group, Inc., which received payment for contracted research from Bristol-Myers Squibb: Bristol-Myers Squibb. S. Rao: Full / Part-time employment: Bristol-Myers Squibb. K. Gupte-Singh: Full / Part-time employment: Bristol-Myers Squibb. M. Rutstein: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb. M.K. Higashi: Full / Part-time employment: Bristol-Myers Squibb. L. Schwartzberg: Advisory / Consultancy: Genentech; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Helsinn; Advisory / Consultancy: Merck; Advisory / Consultancy, Research grant / Funding (institution): Amgen; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Bristol-Myers Squibb.